2018
DOI: 10.1007/s00792-018-1013-z
|View full text |Cite
|
Sign up to set email alerts
|

Halobacterium salinarum storage and rehydration after spray drying and optimization of the processes for preservation of carotenoids

Abstract: Spray drying is appropriate for the preservation of halophilic microorganisms due to the nature of these microorganisms, as they survive in adverse environmental conditions by being encapsulated in salt crystals. Artificial neural networks were in this study used to optimize practically significant spray-drying regimes of the C-carotenoids producer Halobacterium salinarum. Immediately after drying, the samples contained up to 54% halobacterial biomass and less than 5% moisture, and the level of preservation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Halobacteria, which is an extremely halophilic archaea, produces biologically active compounds in response to environmental changes (UV radiation, temperature anomalies, oxidative stress, lack of nutrients, oxygen availability or dehydration) and to interaction with other microorganisms. These biologically active compounds are of widespread interest in several biotechnology industries (Kalenov et al, 2018). Sorokin et al, (2018) reported that strains from extremely halophilic Euryarchaea use insoluble celluloses, cellobiose, as their carbon and energy source.…”
Section: Diversity Of Archaeamentioning
confidence: 99%
“…Halobacteria, which is an extremely halophilic archaea, produces biologically active compounds in response to environmental changes (UV radiation, temperature anomalies, oxidative stress, lack of nutrients, oxygen availability or dehydration) and to interaction with other microorganisms. These biologically active compounds are of widespread interest in several biotechnology industries (Kalenov et al, 2018). Sorokin et al, (2018) reported that strains from extremely halophilic Euryarchaea use insoluble celluloses, cellobiose, as their carbon and energy source.…”
Section: Diversity Of Archaeamentioning
confidence: 99%